An Integral Evaluation of the Financial State of the Regional Enterprises - Kyurdzhiev, Sergey Panteleyevich; Mambetova, Aleksandra Aleksandrovna; Peshkova, Elena Petrovna (Economy of Regions, 2016)
The subject matter of the article is the development of theoretical positions and methodical approaches to the integral evaluation of the financial state of the region’s metallurgical enterprises. The purpose is to show the possibility of dividing the integral evaluation into separate elements for using this tool to build individual models based on the forecasting of the various coordinates of the financial position of enterprise. The hypothesis of the study is based on the objective need to improve the integral evaluation of the financial position of enterprises. This involves the modernization of existing theoretical and methodological approaches to the increase of the quality of analysis by eliminating certain shortcomings of discriminant models in order to clarify the algorithm of constructing the integral index. The methodological bases of systemic approach and mathematical modelling in economics are applied: the methods of financial analysis, grouping, abstraction, comparison which give the possibility of determining the financial indicators needed to build the predictive models of financial state; the methods of correlation and regression analysis, which allow to improve the integral value and to build the mathematical forecasting models. With the purpose of improving the integral evaluation of the financial condition of enterprise, the geometric interpretation is used, which involves the dividing of the integral indicator on the individual elements. The special feature of the proposed methodological approach consists in the implementation rules for the certain procedures of the evaluation of financial position and generalization of the analysis results. The proposed approach can be used by financial analysts to elaborate the strategic plans of company development and structure optimization of financial resources. This research allows to define the quantitative influence of separate parameters on the general assessment of the financial position for the purpose of its forecasting, which is understood as the system of the evidence-based probabilistic assumptions of the basic and alternative structural changes of the enterprise’s assets and liabilities.